ДОСЛІДЖЕННЯ ТЕМПЕРАТУРНОЇ НЕСТАБІЛЬНОСТІ В АКТИВНИХ НВЧ ФІЛЬТРАХ ТА МЕТОДИ ЇЇ ЗМЕНШЕННЯ - Осадчук, О. В.; Осадчук, Я. О.; Лихашорський, С. В. (Вісник Вінницького політехнічного інституту, 2021)
The article presents a study of methods for reducing temperature instability in active microwave filters. The analysis of the effect of temperature on the parameters of an active microwave filter is carried out. The results of experimental studies of the temperature characteristics of microwave filters are also presented. When designing digital systems, especially modern ones that operate with a clock frequency or that use a radio channel in the microwave and microwave range, there is usually a problem of increasing the reliability or reducing the overall size while maintaining high electrical parameters. Requirements for miniaturization of microwave equipment, the task is to create filter circuits that are suitable for integrated production. Unlike low-frequency active filters, when constructing microwave filters, it is necessary to take into account the inertial properties of transistors. Therefore, studies of various stripe active microwave filter circuits exploit reactive phenomena in the transistor. The possibility of their temperature and dynamic stabilization by changing the emitter current of a bipolar transistor is shown. Various circuit solutions for the implementation of this method are proposed. As experimental studies have shown, with increasing temperature, there is a decrease in the filter transfer coefficient at the quasi-resonant frequency. Experimental studies have shown that in order to stabilize the transfer coefficient of temperature rise, an increase in the emitter current is necessary, which can be achieved by a general increase in the supply voltage. Thus, for thermal stabilization of the frequency response of the microwave filter, it is necessary to regulate the current of the transistor emitter simultaneously with the temperature change. The magnitude of the emitter current adjustment when the temperature changes from –60 °C to +100 °C is 3—4 orders of magnitude for low-power silicon transistors.